Systematic Literature Review: Consumption Of Sugary Foods And Beverages In Children And The Increased Risk Of Type 2 Diabetes Mellitus - Priyatin, Lelaning; Sandria, Hafshayu; Amiliana, Aminah; Nurazizah, Dian; Nafisah, Lu'lu; Sistiarani, Colti (Dian Nuswantoro Semarang, 2025)
Type 2 diabetes mellitus (T2DM) in children is becoming an increasing global concern due to its rising prevalence, primarily caused by unhealthy dietary patterns. This study aims to systematically review scientific evidence regarding the relationship between the consumption of sugary foods and beverages and the increased risk of T2DM in children. The method used is a Systematic Literature Review of publications from 2016 to 2025, obtained from databases such as PubMed, ScienceDirect, and Google Scholar. The article selection process followed Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines and resulted in seven studies that met the inclusion and exclusion criteria. The review findings indicate that excessive consumption of sugar-sweetened beverages is strongly associated with an increased risk of T2DM. These findings highlight the importance of early intervention through nutrition education, family involvement, and stricter regulation of unhealthy food and beverage marketing to prevent the development of T2DM in children.